Morphology-inspired low-temperature liquefied petroleum gas sensors of indium oxide. (October 2015) - Jadhav, Vijaykumar V.; Shinde, Dipak V.; Patil, Supriya A.; Liu, Shude; Mutkule, Sandesh U.; Naushad, Mu.; Mane, Rajaram S.; Hui, K.N.; Han, Sung-Hwan
Graphical abstract: Abstract: Low-temperature wet chemical method has been applied to produce indium oxide (In2 O3 ) nanostructures viz. cracked-cubes and the maize-corns which were then employed for their structure, morphology and surface-related measurements and finally envisaged in detection of liquefied petroleum gas (LPG) at different temperatures and concentrations. At 1000 ppm LPG, cracked-cube-based In2 O3 sensor demonstrated lower operating temperature (135 °C) and gas sensitivity (44.35%) than the maize-corn-type (155 °C, 36.51%). Except moderate difference in sensitivity there was negligible difference in response and recovery periods.